Back Cover Image, Volume 119, Number 10, October 2022. Issue 10 (7th September 2022) - Narayanan, Vibha; Rodrigues, Andre L.; Dordick, Jonathan S.
Abstract : The cover image is based on the Article Influence of circadian rhythm on drug metabolism in 3D hepatic spheroids by Vibha Narayanan et al., https://doi.org/10.1002/bit.28180 . Image Credit: Vibha Narayanan.